Influence of preparation method on activity and stability of Ni catalysts supported on Gd doped ceria in dry reforming of methane - Gurav, Hanmant R.; Dama, Srikanth; Samuel, Violet; Chilukuri, Satyanarayana (Journal of CO2 Utilization, 2017)
Nickel catalysts supported on Gd doped ceria (NGDC), with various Ni content, were prepared through different preparation routes and evaluated for dry reforming of methane (DRM). Their detailed characterization revealed that method of preparation plays an important role in Ni dispersion, with catalysts prepared through co-precipitation showing high Ni dispersion. The co-precipitated 12NGDC-cp catalyst with 12 wt% NiO was found to be superior in terms of high CO2 and CH4 conversions compared to catalysts prepared through citrate gel or impregnation methods Even H-2 and CO yields are high on this catalyst, while it shows excellent durability with stable activity even after 100 h on-stream. Thermogravimetric analysis of spent catalyst showed presence of coke, with transmission electron microscopic studies pointing to the presence of Ni crystallites at the mouth of the carbon whiskers. These Ni crystallites appear to be still active for DRM reaction. Among the spent catalysts, the carbon formation was high on catalysts that have bigger Ni crystallites, with the catalysts prepared through impregnation and citrate gel methods having higher coke. Investigations also reveal that the conversion of active (amorphous) carbon into stable (graphitic) carbon depends on the Ni crystallite size, temperature and duration of the reaction. These studies demonstrate that Gd doped ceria is a good support for Ni, to obtain high DRM activity and very good on-stream stability provided the catalysts are prepared through an appropriate method.

Active and durable alkaline earth metal substituted perovskite catalysts for dry reforming of methane - Dama, Srikanth; Ghodke, Seema R.; Bobade, Richa; Gurav, Hanmant R.; Chilukuri, Satyanarayana (Applied Catalysis B - Environmental, 2018)
Dry reforming of methane is an important process for the utilization of CO2 and to get valuable synthesis gas. Alkaline earth metal substituted MZr1-xNixO3-delta perovskites were synthesized by citrate gel method, characterized and evaluated for dry reforming methane. Characterization results show that the type of alkaline earth substituted at the A site of the perovskite oxide plays an important role in terms of structure, basicity, oxygen deficiency and Ni dispersion. Calcium substituted CaZr0.8Ni0.2O3-delta catalyst shows superior activity in terms of high CH4 and CO2 conversion, while maintaining the activity even after 500 h of reaction. Mechanistic investigations were carried out using transient pulse experiments and insitu FTIR-diffuse reflectance spectroscopy. These experiments reveal that redox property and basicity play important role in activation and sustaining the reforming reaction. Insitu FTIR measurements show that surface hydroxyl groups of the support are vital for high activity and durability of CaZr0.8Ni0.2O3-delta catalyst. XRD and TGA analysis of catalysts after reaction show the structures are retained, but peaks pertaining to coke were observed on SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts. On the otherhand, CaZr0.8Ni0.2O3-delta catalyst had only amorphous carbon even after 500 h of reaction. HRTEM studies revealed that SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts deactivated mostly due to the formation of carbon nanotubes with Ni embedded in them. Raman and XPS analysis helped in identifying types of coke precursors present on the catalysts. The investigation also illustrate that type of carbon formed depends on the basicity of perovskite oxide, metal to support interaction, Ni crystallite size, surface hydroxyl groups and oxygen defects. This study clearly demonstrated that CaZr0.8Ni0.2O3-delta is an excellent catalyst for dry reforming reaction with long life.

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Active K-OMS-2 supported catalyst for hydrogenolysis of glycerol - Gogoi, Pranjal; Chilukuri, Satyanarayana; Thirumalaiswamy, Raja (ChemistrySelect, 2021)
Propanediols are very important chemical intermediates, which need to be prepared through commercially viable routes. Cryptomelane type octahedral molecular sieve-2 (K-OMS-2), a cheap and environmentally benign microporous oxide was employed to support Ru and used as a catalyst to get 1,2-propanediol (1,2-PDO) selectively through hydrogenolysis of glycerol. Three catalysts with different Ru content were prepared and evaluated for glycerol hydrogenolysis. Among these, 1 wt.% Ru-K-OMS-2 showed reasonably good activity towards 1,2-PDO formation under moderate reaction conditions even at lower Ru loading (0.9 wt.%). When other metals such as Cu and Ni were supported on K-OMS-2, their performance was inferior compared to Ru-supported catalysts. All the catalysts were characterized using various physicochemical techniques like XRD, N-2-sorption, TPD, H-2-TPR, TGA, ICP-OES, FE-SEM and TEM. The enhanced catalytic activity with the 1 wt.%Ru-K-OMS-2 catalyst was attributed to the better Ru metal dispersion, higher active metal surface area, basic strength, and porosity of the support. The catalyst was found to be recyclable. Analysis of spent catalyst by TEM showed disintegration of Ru nanoparticles to smaller ones, under high H-2 pressure at the reaction temperature. Smaller Ru particles are expected to promote C-C bond cleavage thus suppressing 1,2-PDO formation. Furthermore, a relationship between the TOF value, Ru nanoparticles size, and the basic strength of the catalysts was established, which provides dipper insight into the different catalytic behavior of the catalysts.
Keywords: Glycerol; Hydrogenolysis; octahedral molecular sieves; Propanediols; selectivity